Implementation of geriatric assessment and decision support in residential care homes: facilitating and impeding factors during initial and maintenance phase - Boorsma, Marijke (BioMed Central, 2013)
BACKGROUND: Successfully introducing and maintaining care innovations may depend on the interplay between care setting, the intervention and specific circumstances. We studied the factors influencing the introduction and maintenance of a Multidisciplinary Integrated Care model in 10 Dutch residential care homes. METHODS: Facilitating and impeding factors were studied and compared at the time of introduction of the interRAI-LTCF assessment method in residential care homes as well as three years later, by surveys and semi structured interviews among nurse staff, managers, and physicians. RESULTS: Facilitating factors at introduction were positive opinions of staff and family physicians about the changes of the process of care and the anticipated improvement of quality of care. Staff was positive about the applicability of the software to support the interRAI-LTCF assessments. Impeding factors were time constraints to complete interRAI-LTCF assessments and insufficient computer equipment. In the maintenance phase, the positive attitude of the location manager and the perceived benefits of the care model and the interRAI-LTCF assessment method were most important. Impeding factors after 3 years remained the lack of time to complete the assessments and lack of sufficient computer equipment. CONCLUSIONS: Impeding and facilitating factors were comparable in the initial and maintenance phase. Adoption of the interRAI-LTCF assessment method depended on positive opinions of staff and management, continuing support of staff and the availability of sufficient computer equipment.